Peran Badan Restorasi Gambut Dan Mangrove Dalam Perspektif LingkunganPeran Badan Restorasi Gambut Dan Mangrove Dalam Perspektif Lingkungan - Francisca Devina Putri Guntur; Sapto Hermawan; Asianto Nugroho (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study examines the role of the Peatland and Mangrove Restoration Agency (BRGM) in the environmental context of Indonesia. Based on the analysis of factors strengthening community institutions, BRGM's strategic objectives for 2021-2024, key performance indicators for BRGM in 2023, and future challenges, this research concludes that BRGM plays a crucial role in advocating for the sustainability of peatland and mangrove ecosystems. Through its commitment to supporting peatland restoration, mangrove rehabilitation, community empowerment, and enhancing good governance, BRGM aims to address complex environmental and social challenges in the future. The implications of this research highlight the importance of collaboration between the government, private sector, and communities in preserving natural ecosystems and enhancing collective well-being.